Detection and quantification of Heavy metal and toxins in rice bran related products - Haque, Md. Anwarul; Nilufa Ferdous,; Shozib, Habibul Bari; Shamima Akter, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
This study was aimed to investigate heavy metals and toxins effect on rice bran related industrial products such as rice bran (RB), rice bran oil (RBO) and deoiled rice bran (DORB). Heavy metals such as As, Pb, Cd, Cr, Ni, bacteriological assay such as bacterial load (cfu/g), fungal assay such as yeast and molds load (cfu/g) and fungal toxins specially aflatoxins (B1, B2, Gl and G2) were investigated for RB, RBO and DORB samples. RB and DORB samples were found positive for bacteria, yeast and mold population, and aflatoxin B1 for fresh (0), 7, 14 and 21 days after storage at ambient temperature. RB and DORB samples for 28 days after storage found lower load in bacteria, yeast and mold but completely negative for aflatoxin B1. We have examined all the above mentioned quality parameters for RBO and found negative for bacteria, yeast and mold load and even aflatoxin B1.